Effect of mycorrhiza (glomus intraradices), on the yield of two potato varieties (solanum tuberosum l.) in the highlands of Puno, Peru - Luna Quecaño, Juan Carlos (2020)
Excessive use of chemical fertilizers and pesticides have negative consequences, not friendly to the environment, on the other hand, the use of organic fertilizers (mycorrhizal fungi) is an alternative for healthy agriculture, conserving biodiversity, and above all respecting our planet. The research was carried out in Puno 3,820 meters above sea level, with the aim of determining the effect of the application of mycorrhizal fungus, arbuscular vesicle, (Glomus intraradices) such as MicorrizaFer, on the yield of potato cultivation (Solanum tuberosum L.) in two black Imilla varieties and Compis, in drying conditions during the 2015–2016 agricultural campaign. The research methodology is experimental, descriptive and sequential. Five doses were applied: 1,00; 0,75; 0,50; 0,25 and 0,00 g per plant, prior inoculation of the mycorrhizal fungus on the tuber. For the distribution of treatments, select the Random Complete Block (BCA) design, and the data will be analyzed under a 2 x 5 factorial arrangement, varieties and doses, with three repetitions; the yield was determined by the gravimetric method. The result indicates that the highest yield is obtained with the dose of 1,00 g of Micorriza for plant, 14,01 t.ha-1 in the Imilla Negra variety and 13,82 t.ha-1 in the Compis variety, being higher than the control in 7,02% and 5,97% respectively. without adding chemical fertilization or chemical control of pests and diseases. Factors that could undermine the results of the investigation would be attributed to the altitude at which the investigation was conducted at 3,820 meters above sea level.